Parents’ Knowledge, Perception, and Attitudes Towards Speech and Language Therapy Services of Individuals with Cerebral Palsy: A Quantitative Analysis - Lawal, Ahmed Olaitan; Oyenuga, Foluke Abiodun; Jacob, Udeme Samuel; Pillay, Jace (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
This study examines the relationship between parental knowledge, perception, and attitudes toward speech and language therapy for children with cerebral palsy. The study adopted a descriptive research design of correlational type. Purposive sampling was used to identify fifty parents of individuals with cerebral palsy as respondents in the Ibadan metropolis, Nigeria. Self-structured questionnaires on parental knowledge, perception, and attitudes toward speech and language therapy were used for data collection from the respondents. The findings revealed that parents had moderate knowledge about speech and language therapy, with varying levels of perception and attitudes toward speech and language therapy. The study's limitations include the small sample size, sampling bias, self-reported data, and limited geographic scope. These limitations should be considered when interpreting the study's findings. Despite these constraints, this research provides valuable insights into the complexities of parental perspectives on speech and language therapy for children with cerebral palsy. It highlights the need for further exploration in this area. Future research should address these limitations to understand parental experiences and perspectives in diverse contexts comprehensively.